Media market concentration and pluralism - Torben Stühmeier (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2016)
Media market structures are changing constantly. Traditional media outlets such as newspapers are being hard-hit by the digitalization of content, causing market exit and long-term consolidation in many countries. Competition policy in media markets is not only concerned with this trend because of reduced economic competition, but also because of potentially reduced pluralism. Accordingly, this paper analyzes the relationship between media market concentration and pluralism. In particular, we distinguish between internal pluralism, namely the range of views o.ered by a single outlet, and external pluralism, which refers to the market supply of pluralism. We show that internal pluralism is high in concentrated markets, but external pluralism is not. Moreover, a monopoly market does not necessarily o.er less pluralism than a competitive one.
Keywords: L13; L82; 330; Advertising; Concentration; Media market; Pluralism; Twosided market